The Effect of Covid-19 on Working Capital Strategy and Profitability - Abdul Basyith; Fitriya (International Journal of Social Science and Business, 2023)
Covid-19 disrupted all sectors and caused uncertainty in the market, corporate liquidity crisis, high debt, higher stock volatility, and lower profitability, so this study investigated the effect of working capital strategies on profitability before and during Covid-19 companies listed on the Indonesia Stock Exchange. The populations used in this study are the tourism sector, pharmaceutical sector, and telecommunications. The total sample used was 20 companies selected by purposive sampling method. This data is collected from the financial statements of Q2 2018 to Q3 2021 (14 periods). The data were analyzed using multiple linear regression analysis with dummy variables. The results showed that Cash Conversion Cycle (CCC), Working Capital Investment Approach (WCIA), and Working Capital Financial Approach (WCFA) had a significant effect on Return on Assets (ROA) and Return on Equity (ROE). The result implies that the company must maintain sufficient cash and have good working capital management so that, in the event of a disaster, the company can maintain its performance. The implication of this study is that companies must pay attention and manage their working capital well to achieve higher levels of profitability amid market uncertainty.